Methods to improve the recruitment of holm-oak seedlings in grazed Mediterranean savanna-like ecosystems (dehesas) - Leiva, María José; Mancilla-Leyton, Juan Manuel; Martín-Vicente, Ángel (Annals of Forest Science, 2012)
& Context “Dehesas” are savanna-like ecosystems of human origin that extend broadly in the Mediterranean area of the Iberian Peninsula. They consist of scattered oaks (mainly Quercus ilex subsp. ballota L. holm-oak), an annual grassland layer and interspersed shrubs. These ecosystems, used for grazing and wild game, support high plant and animal biodiversity and provide important environmental services. At present, Mediterranean “dehesas” are endangered by the lack of oak regeneration. & Aims This paper analyses the efficiency of: (1) using shrubs as nurse plants; (2) drip irrigation of seedlings during summer; and (3) a combination of the two methods for the restoration of a “dehesa” in a mid-mountain Mediterranean area of southern Spain. & Methods Different techniques were tested to improve the recruitment of holm-oak seedling during a 3-year field experiment: (1) acorn plantation in open spaces, irrigating seedlings during the first dry season; (2) acorn plantation beneath the canopy of Myrtus communis L. and (3) both methods combined. & Results There was a large facilitative effect of myrtle for the recruitment of holm-oak seedlings, regardless of the supply of irrigation. This effect was associated with a large decrease in air temperature and photosynthetically active radiation beneath myrtle canopies. By contrast, summer irrigation of seedlings planted in open spaces did not improve seedling survival after 3 years despite a small and transient positive effect on seedling survival during the 1st year. & Conclusion The use of evergreen shrubs, such as myrtle, as nurse plants may be considered to restore “dehesas” instead of expensive seedling irrigation techniques. Several studies have promoted abandoning grazing to increase holm oak selfregeneration in “dehesas”. However, creating closed patches of naturally occurring evergreen shrubs could provide suitable sites for oak planting when necessary, thus enhancing seedling recruitment without damaging the environmental and economic value of these ecosystems.
Keywords: nurse plant; Photosynthetically active radiation; seedling emergence timing; seedling longevity; summer drip-irrigation of seedlings

Methods to improve the recruitment of holm-oak seedlings in grazed Mediterranean savanna-like ecosystems (dehesas) - Leiva, María José; Mancilla-Leyton, Juan Manuel; Martín-Vicente, Ángel (Annals of Forest Science, 2012)
& Context “Dehesas” are savanna-like ecosystems of human origin that extend broadly in the Mediterranean area of the Iberian Peninsula. They consist of scattered oaks (mainly Quercus ilex subsp. ballota L. holm-oak), an annual grassland layer and interspersed shrubs. These ecosystems, used for grazing and wild game, support high plant and animal biodiversity and provide important environmental services. At present, Mediterranean “dehesas” are endangered by the lack of oak regeneration. & Aims This paper analyses the efficiency of: (1) using shrubs as nurse plants; (2) drip irrigation of seedlings during summer; and (3) a combination of the two methods for the restoration of a “dehesa” in a mid-mountain Mediterranean area of southern Spain. & Methods Different techniques were tested to improve the recruitment of holm-oak seedling during a 3-year field experiment: (1) acorn plantation in open spaces, irrigating seedlings during the first dry season; (2) acorn plantation beneath the canopy of Myrtus communis L. and (3) both methods combined. & Results There was a large facilitative effect of myrtle for the recruitment of holm-oak seedlings, regardless of the supply of irrigation. This effect was associated with a large decrease in air temperature and photosynthetically active radiation beneath myrtle canopies. By contrast, summer irrigation of seedlings planted in open spaces did not improve seedling survival after 3 years despite a small and transient positive effect on seedling survival during the 1st year. & Conclusion The use of evergreen shrubs, such as myrtle, as nurse plants may be considered to restore “dehesas” instead of expensive seedling irrigation techniques. Several studies have promoted abandoning grazing to increase holm oak selfregeneration in “dehesas”. However, creating closed patches of naturally occurring evergreen shrubs could provide suitable sites for oak planting when necessary, thus enhancing seedling recruitment without damaging the environmental and economic value of these ecosystems.
Keywords: nurse plant; Photosynthetically active radiation; seedling emergence timing; seedling longevity; summer drip-irrigation of seedlings

Holm-oak (Quercus ilex subsp. Ballota) acorns infestation by insects in Mediterranean dehesas and shrublands - Leiva, María José; Fernández-Alés, Rocío (Forest Ecology and Management, 2005)
The aim of this study is to know if acorn predation by insects is limiting the sexual regeneration of holm-oak in Mediterranean dehesas and if this process plays the same or a different role in these human-managed ecosystems and in adjacent Mediterranean shrublands which are much less intensively transformed and exploited by man than Mediterranean dehesas. We conducted the study in Southern Spain, in three sites containing dehesas and in three sites containing Mediterranean shrublands and included a total of 90 holm-oak trees (15 holm-oak trees per site) and 4500 acorns (50 acorns per tree). The weevil Curculio elephas and the moth Cydia fagiglandana were the insect species that predated the acorns collected from our sites. The per-tree mean percentage of insect-infested acorns was 16.6% for the whole set of trees included in the study. However, at any given site, variability in the infestation rate among individual trees was very high (i.e., 2–72% and 0–32% infested acorns per tree in the most and less variable sites, respectively). There were signiﬁcant differences in the infestation rate among the studied sites. However, these differences were not related to the ecosystem type as the group of sites that experienced the lowest signiﬁcant infestation rate (10–16% infested acorns per tree in average) were occupied either by dehesas or by shrublands and the same was true for the group of sites that experienced the highest signiﬁcant infestation rate (16–30% infested acorns per tree in average). Infested acorns experienced a 15% decreased in viability (i.e., acorn germination and seedling emergence) comparative to sound acorns. Combining this rate and the mean per-tree average rate of acorn infestation resulted in a 2.5% failures in seedling recruitment due to insect infestation for the whole studied area. We conclude that the effect of pre-dispersive seed predation on seedling recruitment is very low in average, although it likely varies moderately (i.e., from 1.5% to 4.5%) among sites. Current management in dehesas i.e., regular pruning of holm-oak trees and high consumption of the acorn crop by livestock from year to year, does not control pre-dispersive acorn predation by weevils and moths and thus, it does not contribute to explain the poor self-regeneration of the holm-oak trees in these ecosystems comparative to adjacent Mediterranean shrublands.
Keywords: holm-oak self-regeneration; moths; pre-dispersive acorn predation; tree-to-tree variability in acorndry weight and in; weevils

Holm-oak (Quercus ilex subsp. Ballota) acorns infestation by insects in Mediterranean dehesas and shrublands - Leiva, María José; Fernández-Alés, Rocío (Forest Ecology and Management, 2005)
The aim of this study is to know if acorn predation by insects is limiting the sexual regeneration of holm-oak in Mediterranean dehesas and if this process plays the same or a different role in these human-managed ecosystems and in adjacent Mediterranean shrublands which are much less intensively transformed and exploited by man than Mediterranean dehesas. We conducted the study in Southern Spain, in three sites containing dehesas and in three sites containing Mediterranean shrublands and included a total of 90 holm-oak trees (15 holm-oak trees per site) and 4500 acorns (50 acorns per tree). The weevil Curculio elephas and the moth Cydia fagiglandana were the insect species that predated the acorns collected from our sites. The per-tree mean percentage of insect-infested acorns was 16.6% for the whole set of trees included in the study. However, at any given site, variability in the infestation rate among individual trees was very high (i.e., 2–72% and 0–32% infested acorns per tree in the most and less variable sites, respectively). There were signiﬁcant differences in the infestation rate among the studied sites. However, these differences were not related to the ecosystem type as the group of sites that experienced the lowest signiﬁcant infestation rate (10–16% infested acorns per tree in average) were occupied either by dehesas or by shrublands and the same was true for the group of sites that experienced the highest signiﬁcant infestation rate (16–30% infested acorns per tree in average). Infested acorns experienced a 15% decreased in viability (i.e., acorn germination and seedling emergence) comparative to sound acorns. Combining this rate and the mean per-tree average rate of acorn infestation resulted in a 2.5% failures in seedling recruitment due to insect infestation for the whole studied area. We conclude that the effect of pre-dispersive seed predation on seedling recruitment is very low in average, although it likely varies moderately (i.e., from 1.5% to 4.5%) among sites. Current management in dehesas i.e., regular pruning of holm-oak trees and high consumption of the acorn crop by livestock from year to year, does not control pre-dispersive acorn predation by weevils and moths and thus, it does not contribute to explain the poor self-regeneration of the holm-oak trees in these ecosystems comparative to adjacent Mediterranean shrublands.
Keywords: holm-oak self-regeneration; moths; pre-dispersive acorn predation; tree-to-tree variability in acorndry weight and in; weevils

Variability in seedling water status during drought within a Quercus ilex subsp. ballota population, and its relation to seedling morphology - Leiva, María José; Fernández-Alés, Rocı́o (Forest Ecology and Management, 1998)
Differences in morphology, growth and plant water status during drought were studied in greenhouse-grown Quercus ilex subsp. ballota seedlings produced by different mother trees occurring in a savannah-like forest (locally named dehesa) in southern Spain. There were signi®cant differences among mother trees in the biomass of their seeds (mother tree level accounted for 62% of total variance in this trait), in the percentage of seedlings that emerged and in the time of shoot emergence. The progeny that had high emergence rates (80±90%) also had short emergence times while the opposite was true for the progeny that had low (43%) and intermediate (70%) emergence rates. Acorn biomass covaried signi®cantly with seedling total biomass and with the biomass of different parts of the seedlings, but not with the partitioning of biomass among roots and shoots (root/shoot ratio) nor to morphological seedling traits such as shoot height, total leaf area, average leaf size, speci®c leaf area (SLA) and leaf number. All these traits varied signi®cantly among the seedlings produced by different mother trees. The conductance to water vapour (glw) of the foliage of the seedlings also varied signi®cantly among mother trees and was dependent on the root/shoot ratio as on the total leaf area of the seedlings, but not on the total seedling biomass. One of the six trees that were studied produced seedlings which had a signi®cantly higher root/shoot ratio, smaller leaf area, smaller leaves, higher speci®c leaf area and shorter stems than the seedlings produced by any other tree. In addition, the former set of seedlings had signi®cantly higher glw 15 and 30 days after drought, and higher leaf water content at the end of the experiment than the other seedlings. We discuss the value of using single seedling traits related to drought tolerance such as root/shoot ratio and leaf area in the framework of the restoration of savannah-like oak forest in the Mediterranean areas. We also discuss the functional implications of the diversity of genotypes within the oak populations in the framework of the global climate change
Keywords: Drought tolerance; Holm oak; root/shoot ratio; savannah-like forest; seedling biomass